Konkurence dopravních firem z pohledu globalizace a regionalizace - Bauer, Romuald; Marciszewska, Elżbieta (Univerzita Pardubice, 2001)
The globalization and regionalisation processes involve almost all the cultural, social and economic sphere of life. They have owned promoters and adversaries both of these frends. The globalisation as an economic process come through three levels:¦the firm level, ¦the branch level, ¦the world economics level. The presented trends will have the basic sense for the Poland and Poland's firms including the transport firms. Process has an objective character and there is the way to find their utilisation for the benefit of all society. The EU integration, the economics transformation and the transformation of the firm complicate species interaction between the globalisation and regionalisation.The article deals with globalisation and regionalisation process on the level of transport firm and transport branch level. At judge of mentioned process in the Poland's conditions, there is pay attention to the air, road and railway firms. Authors of the article started from the official document "The Purpose of the Poland State Policy of Transportation in the 2000-2015 Period" partly.In the air transport is the globalisation enterprise admittance of PLL LOT, a.s. to the Qualiflyer alliance. It is possible rate as a building element of the carrier global strategy. Together with it is needed to build up the net of regional airports too. Concerning the railway transport (PKP), there obtained the regionalisation tendency. This is the outcome of the railway attribute and the process of transformation. On the other site the European integration process in the railway area must take ento account the globalisation requirements. In the road transport there is the problem of the large number of the carriers with the mentioned view. There enacted the differeniation of the firms on the regional and European trasport market. Will dominate the tendency to the regionalsation in the road transport too.
Keywords: dopravní firmy; Polsko; regionalizace; globalizace; Konkurence